Anterior open bite correction by Le Fort I osteotomy with or without anterior segmentation: which is more stable? - Ismail, Izzati Nabilah Ismail; Leung, Y.Y. (Elsevier, 2017)
A retrospective cohort study was conducted to analyze the relapse rate of anterior open bite (AOB) correction comparing Le Fort I osteotomy with and without anterior segmentation. The risk factors that might contribute to relapse were also assessed. Lateral cephalograms obtained at six different times were analyzed. A total of 81 patients with AOB were recruited. Thirty-five patients underwent Le Fort I osteotomy without anterior segmentation and 46 patients underwent anterior segmentation. Le Fort I osteotomy with anterior segmentation resulted in significantly more AOB relapse when compared to that without anterior segmentation at 7 weeks postoperative (15.2% vs. 0%, P = 0.016). During the early postoperative period, factors that contributed to AOB relapse in Le Fort I osteotomy with anterior segmentation were AOB closure 4 mm and inferior positioning of the anterior segment >2 mm. Over the long term, AOB closure 4 mm and intraoral vertical ramus osteotomy as the only mandibular procedure were factors identified as causing more AOB relapse in those treated by Le Fort I osteotomy with anterior segmentation. In conclusion, Le Fort I osteotomy without anterior segmentation was found to be more stable in the surgical correction of AOB in the early and late postoperative periods.